A coconut leaf sheath derived graphitized n‐doped carbon network for high‐performance supercapacitors - Jayakumar, Anjali (2020)
A highly graphitized nitrogen‐doped carbon network is synthesized from biomass, obtained from coconut tree leaf sheath and successfully demonstrates high energy storage properties for use in supercapacitors. A simple thermal physical activation in carbon dioxide atmosphere also enables the electrochemical activity of the carbon to be improved. A detailed study is carried out to understand the dependence of the electrochemical performance on parameters such as the concentration of urea used for doping, the activation temperature, and time of activation. An optimized sample is obtained to give a very high electrochemical performance. Our best sample, obtained by using a 0.5 M urea solution for doping, annealed at 700 °C under a N2 atmosphere and activated at an activation temperature of 800 °C under a CO2 atmosphere, named 0.5 M‐700 N‐800C, gave a very high specific capacitance of 360.9 F g−1 in 2 M KOH in the potential window of 0 to −1.1 V. This performance as a negative electrode exceeds the specific capacitance of graphene hydrogels (305 F g−1) that we prepared and is more than that of commercially available activated carbon 218.18 F g−1. Thus, it brings to light the possibility of using our material as an efficient, cheap substitute for negative electrode materials like graphene, carbon nanotubes, and activated carbon. This process is facile, extremely cheap, and environmental friendly, which utilizes urea, a non‐hazardous nitrogen dopant.